Mechanistic Model for UV light-enhanced NO2 Sensing utilizing Ordered Mesoporous In2O3 - Wagner, Thorsten; Tiemann, Michael; Kohl, Claus-Dieter; Morandi, Sara; Malagù, Cesare; Donato, Nicola; Latino, Mariangela; Neri, Giovanni (Proceedings IMCS 2012)

Nanostructured Metal Oxides for High-Temperature Gas Sensing: Structural Stabilization in Porous Metal Oxides - Klaus, Dominik; Tiemann, Michael; Wagner, Thorsten (Proceedings IMCS 2012)

Second-Person Narration in Literary and Conversational Storytelling - Mildorf, Jarmila (Storyworlds)

Imaginary Dialogues in English: Explorations of a Literary Form

New Perspectives on Imaginary Dialogues: An Interdisciplinary Dialogue - Kinzel, Till; Mildorf, Jarmila (Imaginary Dialogues in English: Explorations of a Literary Form)

Polite Conversation, Implicatures, and Comical Effect: Jonathan Swift and P. G. Wodehouse - Mildorf, Jarmila (Imaginary Dialogues in English: Explorations of a Literary Form)

Karl Popper’s Debt to Leonard Nelson - Milkov, Nikolay (Grazer philosophische Studien)

The Beginnings of Model Theory in the Algebra of Logic - Peckhaus, Volker (Probabilities, Laws, and Structures)
Rezension: Zbl. Math. 1316.00023 (D. Bondoni)

Dressed for Success: Lifestyle and The L Word - Strube, Miriam (Banale Kämpfe? Perspektiven auf Populärkultur und Geschlecht)

Born to be wild? Dead Man, The New World and Filmic Revisionism - Strube, Miriam (Visual Representations of Native Americans: Transnational Contexts and Perspectives)

'Life is in the Transitions’: Revisiting William James’s Pragmatism - Strube, Miriam; Rohr, Susanne (Revisiting Pragmatism: William James in the New Millennium)

Negating Domination: Pragmatism, Pluralism, Power - Strube, Miriam (Revisiting Pragmatism: William James in the New Millennium)

Condensation of an ideal gas with intermediate statistics on the horizon - Zare, Somayeh; Raissi, Zahra; Mohammadzadeh, Hosein; Mirza, Behrouz (The European Physical Journal C)

Mathematik - Ein Reiseführer - Hilgert, Joachim; Hilgert, Ingrid

Integration im und durch Sport. Die sportpolitische Programmatik in Deutschland aus sportwissenschaftlicher Perspektive - Grimminger-Seidensticker, Elke; Gieß-Stüber, P. (Revue d´Allemagne et des Pays de Langue Allemande)

An Empirical Study About the Importance of Teachers´ Educational Beliefs and Acculturation Attitudes for the Implementation of Intercultural Education in Physical Education - Grimminger-Seidensticker, Elke (Journal of Physical Education and Health. Social Perspective)

Anerkennungs- und Missachtungsprozesse im Sportunterricht. Die Bedeutung von Machtquellen für die Gestaltung sozialer Peer-Beziehungen - Grimminger-Seidensticker, Elke (Sportwissenschaft)

Von Menschenfängern und Menschenfischern. Sklaverei und Loskauf im Kirchenstaat des 16.–18. Jahrhunderts - Priesching, Nicole

Music Encoding Initiative Guidelines Version 2.0.0 - Kepper, Johannes; Roland, Perry D.

Neue Wege der Musikerschließung. Über den möglichen Einsatz von MEI in deutschen Bibliotheken - Hartwig, Maja; Kepper, Johannes; Richts, Kristina (Forum Musikbibliothek)